Evaluasi Kebijakan Pengendalian Pencemaran Udara Dalam Upaya Meningkatkan Kualitas Udara DKI Jakarta - Deshermansyah Deshermansyah (Universitas Negeri Jakarta, 2016)
This research aimed to evaluate the implementation of the Jakarta Regional Government Policy, Regional Regulation Number 2 of 2005 regarding Air Pollution Controlling is still valid. Evaluation results are expected to provide recommendations to the local government of Jakarta to repair/ improvement implementation, as well as making policy recommendations on control of air pollution that can be used as a reference for local governments and communities of Jakarta, and ensure the maintenance of wakefulness and air quality. This is a policy research study, the research design to follow the model of Haas & Springer. Data collection activities carried out following the opinion Majchrzak and data analysis techniques using focused synthesis. From the research, suggests that the local government has not been able to implement the Jakarta DKI Jakarta Regional Regulation Number 2 of 2005 effectively and efficiently